Indian women in librarianship - Samantaray, M. (Moorttimatee) (New Delhi : National Book Organisation, 1998)
Study confined to university libraries of eastern India.
Includes bibliographical references (p. [159]-175) and index.
Keywords: Women in library science -- India; Women librarians -- India; Women in information science -- India